Clinical Factors and Outcomes of Atypical Meningioma: A Population-Based Study - Zhang, Gui-Jun; Liu, Xiao-Yin; You, Chao (Frontiers in Oncology, 2021)
Abstract Objective Atypical meningioma is a non-benign tumor, and its prognostic factors and treatment strategies are unclear reported. Methods Patients with atypical meningioma, between 2004 and 2016, were collected from the Surveillance, Epidemiology, and End Results database. Then, we randomly divided patients into a training set and a validation set at a ratio of 8:2. The nomograms was constructed based on the multivariate Cox regression analyses, and the concordance index, calibration curves, and receiver operating character were used to assess the predictive ability of the nomogram. We divided the patient scores into three groups and constructed a survival curve using kaplan–meier analysis. Results After our inclusion and exclusion criteria, 2358 patients with histologically-identified atypical meningioma. The prognostic nomogram that comprised factors of overall survival, including age, tumor size and surgery. the C-index was 0.715 (95%CI=0.688-0.742) for overall survival in the training set and 0.688 (95%CI=0.629-0.747) for overall survival in the validation set. The calibration curves and receiver operating character also indicated the good predictability of the nomogram. Risk stratification revealed a statistically significant difference among the three groups of patients divided according to quartiles of risk score. Conclusion gross total resection is an independent factor for survival, and radiation after non-gross total resection potentially conferred a survival advantage for patients with atypical meningioma.